Oral and Gastric Helicobacter Pylori: Effects and Associations - Veiga, Nélio Jorge (2018)
Introduction This study consisted in the comparison of the prevalence of Helicobacter pylori (H. pylori) present in the stomach and in saliva of a sample of Portuguese adolescents and the assessment of the association between H. pylori infection with socio-demographic variables and prevalence of dental caries. Materials and Methods A cross-sectional study was designed including a sample of 447 adolescents aged 12 to 19 years old, attending a public school in Sátão, Portugal. A questionnaire about socio-demographic variables and oral health behaviors was applied. Gastric H. pylori infection was determined using the urease breath test (UBT). Saliva collection was obtained and DNA was extracted by Polymerase Chain Reaction (PCR) in order to detect the presence of oral H. pylori. Results The prevalence of gastric H. pylori detected by UBT was 35.9%. Within the adolescents with a gastric UBT positive, only 1.9% were positive for oral H. pylori. The presence of gastric H. pylori was found to be associated with age (>15years, Odds ratio (OR)=1.64,95%CI=1.08-2.52), residence area (urban,OR=1.48,95%CI=1.03-2.29) and parents´ professional situation (unemployed,OR=1.22,95%CI=1.02-1.23). Among those with detected dental caries during the intra-oral observation, 37.4% were positive for gastric H. pylori and 40.2% negative for the same bacterial strain (p=0.3). Conclusions The oral cavity cannot be considered a reservoir for infection of H. pylori. Gastric H. pylori infection was found to be associated with socio-demographic variables such as age, residence area and socioeconomic status.